Efficient demultiplexed single-photon source with a quantum dot coupled to a nanophotonic waveguide - Hummel, Thomas; Ouellet-Plamondon, Claudéric; Ugur, Ela; Kulkova, Irina; Lund-Hansen, Toke; Broome, Matthew A.; Uppu, Ravitej; Lodahl, Peter (Applied Physics Letters)
Planar nanostructures allow near-ideal extraction of emission from a quantum emitter embedded within, thereby realizing deterministic single-photon sources. Such a source can be transformed into M single-photon sources by implementing active temporal-to-spatial mode demultiplexing. We report on the realization of such a demultiplexed source based on a quantum dot embedded in a nanophotonic waveguide. Efficient outcoupling (>60%) from the waveguide into a single mode optical fiber is obtained with high-efficiency grating couplers. As a proof-of-concept, active demultiplexing into M = 4 spatial channels is demonstrated by the use of electro-optic modulators with an end-to-end efficiency of >81% into single-mode fibers. Overall, we demonstrate four-photon coincidence rates of >1 Hz even under nonresonant excitation of the quantum dot. The main limitation of the current source is the residual population of other exciton transitions, which corresponds to a finite preparation efficiency of the desired transition. We quantitatively extract a preparation efficiency of 15% using the second-order correlation function measurements. The experiment highlights the applicability of planar nanostructures as efficient multiphoton sources through temporal-to-spatial demultiplexing and lays out a clear path way of how to scale up toward demonstrating quantum advantages with the quantum dot sources.

Streak camera imaging of single photons at telecom wavelength - Allgaier, Markus; Ansari, Vahid; Eigner, Christof; Quiring, Viktor; Ricken, Raimund; Donohue, John Matthew; Czerniuk, Thomas; Aßmann, Marc; Bayer, Manfred; Brecht, Benjamin; Silberhorn, Christine (Applied Physics Letters)

Noble metal free photocatalytic H2 generation on black TiO2: On the influence of crystal facets vs. crystal damage - Liu, Ning; Steinrück, Hans-Georg; Osvet, Andres; Yang, Yuyun; Schmuki, Patrik (Applied Physics Letters)

Controlling the optical spin Hall effect with light - Lafont, O.; Luk, S. M. H.; Lewandowski, P.; Kwong, N. H.; Leung, P. T.; Galopin, E.; Lemaitre, A.; Tignon, J.; Schumacher, Stefan; Baudin, E.; Binder, R. (Applied Physics Letters)

Species transport on the target during high power impulse magnetron sputtering - Layes, V.; Monje, S.; Corbella, C.; Trieschmann, J.; de los Arcos de Pedro, Maria Teresa; von Keudell, A. (Applied Physics Letters)

Near infrared Kerr effect and description of field-induced phase transitions in polymer-stabilized blue phase liquid crystals - Atorf, B.; Rasouli, H.; Nordendorf, G.; Wilkes, D.; Kitzerow, Heinz-Siegfried (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

Periodic domain inversion in x-cut single-crystal lithium niobate thin film - Mackwitz, P.; Rüsing, Michael; Berth, Gerhard; Widhalm, A.; Müller, K.; Zrenner, Artur (Applied Physics Letters)
We report the fabrication of periodically poled domain patterns in x-cut lithium niobate thin-film. Here, thin films on insulator have drawn particular attention due to their intrinsic waveguiding properties offering high mode confinement and smaller devices compared to in-diffused waveguides in bulk material. In contrast to z-cut thin film lithium niobate, the x-cut geometry does not require back electrodes for poling. Further, the x-cut geometry grants direct access to the largest nonlinear and electro-optical tensor element, which overall promises smaller devices. The domain inversion was realized via electric field poling utilizing deposited aluminum top electrodes on a stack of LN thin film/SiO2 layer/Bulk LN, which were patterned by optical lithography. The periodic domain inversion was verified by non-invasive confocal second harmonic microscopy. Our results show domain patterns in accordance to the electrode mask layout. The second harmonic signatures can be interpreted in terms of spatially, overlapping domain filaments which start their growth on the þz side.

Ultrafast carrier dynamics and resonant inter-miniband nonlinearity of a cubic GaN/AlN superlattice - Jostmeier, Thorben; Wecker, Tobias; Reuter, Dirk; As, Donat Josef; Betz, Markus (Applied Physics Letters)

Fabrication and characterisation of gallium arsenide ambipolar quantum point contacts - Chen, J. C. H.; Klochan, O.; Micolich, A. P.; Das Gupta, K.; Sfigakis, F.; Ritchie, D. A.; Trunov, K.; Reuter, Dirk; Wieck, A. D.; Hamilton, A. R. (Applied Physics Letters)

Photonic crystal cavities with metallic Schottky contacts - Quiring, W.; Al-Hmoud, M.; Rai, A.; Reuter, Dirk; Wieck, A. D.; Zrenner, Artur (Applied Physics Letters)
We report about the fabrication and analysis of high Q photonic crystal cavities with metallic Schottky-contacts. The structures are based on GaAs n-i membranes with an InGaAs quantum well in the i-region and nanostructured low ohmic metal top-gates. They are designed for photocurrent readout within the cavity and fast electric manipulations. The cavity structures are characterized by photoluminescence and photocurrent spectroscopy under resonant excitation. We find strong cavity resonances in the photocurrent spectra and surprisingly high Q-factors up to 6500. Temperature dependent photocurrent measurements in the region between 4.5K and 310K show an exponential enhancement of the photocurrent signal and an external quantum efficiency up to 0.26.

Impact of nanomechanical resonances on lasing from electrically pumped quantum dot micropillars - Czerniuk, T.; Tepper, J.; Akimov, A. V.; Unsleber, S.; Schneider, C.; Kamp, M.; Höfling, S.; Yakovlev, D. R.; Bayer, M. (Applied Physics Letters)
We use a picosecond acoustics technique to modulate the laser output of electrically pumped GaAs/AlAs micropillar lasers with InGaAs quantum dots. The modulation of the emission wavelength takes place on the frequencies of the nanomechanical extensional and breathing (radial) modes of the micropillars. The amplitude of the modulation for various nanomechanical modes is different for every micropillar which is explained by a various elastic contact between the micropillar walls and polymer environment.

Electrically tunable zero dispersion wavelengths in photonic crystal fibers filled with a dual frequency addressable liquid crystal - Wahle, Markus; Kitzerow, Heinz-Siegfried (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

Confocal shift interferometry of coherent emission from trapped dipolar excitons - Repp, J.; Schinner, G. J.; Schubert, E.; Rai, A. K.; Reuter, Dirk; Wieck, A. D.; Wurstbauer, U.; Kotthaus, J. P.; Holleitner, A. W. (Applied Physics Letters)

Magneto-optical studies of Gd-implanted GaN: No spin alignment of conduction band electrons - Buß, J. H.; Rudolph, J.; Shvarkov, S.; Semond, F.; Reuter, Dirk; Wieck, A. D.; Hägele, D. (Applied Physics Letters)

Whispering gallery modes in zinc-blende AlN microdisks containing non-polar GaN quantum dots - Bürger, M.; Ruth, M.; Declair, S.; Förstner, Jens; Meier, Cedrik; As, Donat Josef (Applied Physics Letters)
Whispering gallery modes (WGMs) were observed in 60 nm thin cubic AlN microdisk resonators containing a single layer of non-polar cubic GaN quantum dots. Freestanding microdisks were patterned by means of electron beam lithography and a two step reactive ion etching process. Micro-photoluminescence spectroscopy investigations were performed for optical characterization. We analyzed the mode spacing for disk diameters ranging from 2-4 lm. Numerical investigations using three dimensional finite difference time domain calculations were in good agreement with the experimental data. Whispering gallery modes of the radial orders 1 and 2 were identified by means of simulated mode field distributions.
Keywords: tet_topic_qd; tet_topic_microdisk

Microresonator-enhanced electroluminescence of an organic light emitting diode based on a columnar liquid crystal - Vollbrecht, Joachim; Kasdorf, Olga; Quiring, Viktor; Suche, Hubertus; Bock, Harald; Kitzerow, Heinz-Siegfried (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

A double-threshold technique for fast time-correspondence imaging - Li, Ming-Fei; Zhang, Yu-Ran; Liu, Xue-Feng; Yao, Xu-Ri; Luo, Kai Hong; Fan, Heng; Wu, Ling-An (Applied Physics Letters)

Magnetic field dependence of the spin relaxation length in spin light-emitting diodes - Höpfner, Henning; Fritsche, Carola; Ludwig, Arne; Ludwig, Astrid; Stromberg, Frank; Wende, Heiko; Keune, Werner; Reuter, Dirk; Wieck, Andreas D.; Gerhardt, Nils C.; Hofmann, Martin R. (Applied Physics Letters)

Momentum matching in the tunneling between 2-dimensional and 0-dimensional electron systems - Beckel, Andreas; Zhou, Daming; Marquardt, Bastian; Reuter, Dirk; Wieck, Andreas D.; Geller, Martin; Lorke, Axel (Applied Physics Letters)

Non-resonant optical excitation of mode-locked electron spin coherence in (In,Ga)As/GaAs quantum dot ensemble - Schwan, A.; Varwig, S.; Greilich, A.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Applied Physics Letters)